KONTRIBUSI KOMPETENSI MEMBACA GAMBAR KERJA TERHADAP HASIL NILAI PRAKERIN SISWA KELAS XII TEKNIK GAMBAR BANGUNAN SMKN 2 PAYAKUMBUH - Dedi Suryadi; M. Giatman, MSIE (CIVED, 2019)
Abstract— This article aims to describe the contribution of competency in reading working drawings for Class XII students in Building Drawing Engineering (TGB) of SMK 2 Payakumbuh to the value’s result of industrial work practices. This type of research is quantitative descriptive. The population in this study were class XII students of the TGB expertise program at SMK 2 Payakumbuh. The number of students is 51 people from 2 classes. The study sample consisted of all students of class XII TGB, totaling 51 people. Sampling uses total sampling. The variables studied were 2 variables. The research instrument used was an objective test question. The number of statements on the question is 31 items. Before the data collection was carried out, a trial was conducted on class XII students of the TGB expertise program at SMKN 1 Tilatang Kamang, amounting to 21 people. This is done to find out whether the instrument is valid and reliable. Data was analyzed manually using Microsoft Excel 2013. The results of the percentage contribution to the competency of reading drawings of work on the results of apprenticeship values have a percentage value of 34.97%.Keywords:Contribution, Competency, Reading Drawing Working, Internship, Technic Building Picture